Republic of Slovenia : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
Slovenia is among the most successful transition economies of central and eastern Europe. The authorities have consistently maintained conservative macroeconomic policies, which together with the relatively favorable starting point, allowed them the luxury of a gradual pace of reform. This approach to economic policy has delivered macroeconomic stability while maintaining social consensus and political continuity; at the same time, however, it has delayed the restructuring in certain sectors. Developments in 1999 have shaped by changes in the external environment and temporary domestic factors.